Objektna tehnologija v sistemih nadzora in vodenja produktne linije SI2000 verzije 5 - Robnik, Ana (Uporabna informatika (Ljubljana), 2000)
Iskratel is a company with long tradition in the development of telecommunications equipment, whereof the result is own product - the SI2000 system. Servers for supervision and management of network and services are a vital upgrade of the Management Node from the SI2000, version 5 product line. They make a functional and communication link between SI2000 and EWSD nodes and business layer as well as 3-rd party applications.
Keywords: Iskratel; komunikacijska infrastruktura; nadzor; omrežja; strežniki; vodenje